Memorandum relating to the provision of free medical attendance and medicine to dependants of men serving with the Colours
1914-10-10 1914 1910s 3 pages Circular to Local Representative Committee in England and Wales Circular 1 (D.M.T.). GOVERNMENT COMMITTEE ON THE PREVENTION AND RELIEF OF DISTRESS. Memorandum relating to the Provision of Free Medical Attendance and Medicine to Dependants of Men serving with the Colours. It will probably be within the knowledge of the Local Representative Committee that the British Medical Association and the Pharmaceutical Society of Great Britain recently addressed a joint letter to the Government stating that, in view of the marked desire shown by doctors and pharmacists throughout the country to be of assistance in the present crisis, they felt justified in promising the co-operation of the Medical and Pharmaceutical Professions in a scheme for the provision of medical attendance without charge, and medicine and appliances at cost price, to dependants of men serving with the Colours, except those whose circumstances are such as to render them unsuitable recipients. The letter further offered the assistance of the Association and the Society in organising the service. This offer has been gratefully accepted, and the Government Committee on the Prevention and Relief of Distress have been in communication on the subject with the National Relief Fund Committee, who have undertaken to defray for the present, out of that Fund, the cost price of the medicine and appliances supplied in connection with the scheme. A special Committee (including representatives of the British Medical Association and the Pharmaceutical Society, with the Duke of Devonshire as Chairman) have been constituted for the purpose of bringing the scheme into operation on a properly organised and comprehensive basis. The necessary arrangements having been made by this Committee, the British Medical Association and Pharmaceutical Society communicated with the individual members of the Medical and Pharmaceutical Professions, informing them of the detailed arrangements adopted and inviting their co-operation. To this appeal a generous response has been received from doctors and chemists in all parts of the country, intimating their willingness to give their services in accordance with the scheme, as set forth overleaf. The cordial co-operation of Local Representative Committees in the scheme is accordingly invited. The special Committee charged with the duty of bringing the scheme into operation will be pleased to advise on any points of difficulty which may arise. Communications should be addressed to "The Joint Secretaries, Naval and Military Dependants (Medical Treatment) Committee, Wellington House, Buckingham Gate, London, S.W." Postage need not be prepaid on communications so addressed. 10th October, 1914. O (33)24332 Pk 169 25,000 10/14 E & S 36/H24/1